Transtheoretical Model-based Nursing Intervention on Lifestyle Change: A Review Focused on Intervention Delivery Methods - Joo Yun Lee, RN; Hyeoun-Ae Park, PhD, RN; Yul Ha Min, PhD, RN (Elsevier, 2015)
Purpose: The transtheoretical model (TTM) was used to provide tailored nursing for lifestyle management such as diet, physical activity, and smoking cessation. The present study aims to assess the provision of intervention delivery methods, intervention elements, and stage-matched interventions, in order to identify ways in which information technology is used in the TTM-based research. Methods: The relevant literature was selected by two researchers using inclusion criteria after searching for "TTM (transtheoretical or stage of change)" and "nursing" from the databases PubMed and CINAHL. The selected studies were categorized in terms of study characteristics, intervention delivery method, intervention element, and use and level of stage-matched intervention. Results: A total of 35 studies were selected including eight studies that used information communication technology (ICT). Nine different intervention delivery methods were used, of which "face-to-face" was the most common at 24 times. Of the 35 studies, 26 provided stage-matched interventions. Seven different intervention elements were used, of which "counseling" was the most common at 27 times. Of all the intervention elements, tailored feedback used ICT the most at seven instances out of nine, and there was a significant difference in the rate of ICT usage among intervention elements. Conclusions: ICT is not yet actively used in the TTM-based nursing interventions. Stage-matched interventions and TTM concepts were shown to be in partial use also in the TTM-based interventions. Therefore, it is necessary to develop a variety of ways to use ICT in tailored nursing interventions and to use TTM frameworks and concepts.